2021
DOI: 10.1038/s41598-021-81623-8
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation and utilisation of nano-reduced starch from underutilised cereals for delivery of folic acid through human GI tract

Abstract: Ball milling offers green approach for size reduction of starch granules to nano scale size. In this research work, the starch from two underutilised cereal varieties viz. foxtail starch (FS) and sorghum starch (SS) were milled to achieve the desired nanometric range with mean particle diameter of 467.98 and 271.12 nm for nano foxtail (FSN) and nano sorghum starch (SSN), which were highly stable as revealed by zeta potential analysis. Functional attributes like solubility, swelling index, apparent amylose cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 54 publications
1
13
0
Order By: Relevance
“…In the case of resistant starch, the presence of large crystals has a significant impact on crystallinity as observed by Ma et al 24 In the case of RS30, RS60, and RS90, a decrease in the intensity of peaks was observed, with a major decrease in the peaks at 2θ of 18.05°, 22°, and 23.05°. A similar decrease in crystallinity of starch nanoparticles obtained after ball milling was observed by Jhan et al, 8,31 with the crystallinity values from 30.23−16.08% and 33.48−18.56% over a typical angle range of 10−45°(angle of diffraction). Ball milling has shown to decrease the crystallinity of materials.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…In the case of resistant starch, the presence of large crystals has a significant impact on crystallinity as observed by Ma et al 24 In the case of RS30, RS60, and RS90, a decrease in the intensity of peaks was observed, with a major decrease in the peaks at 2θ of 18.05°, 22°, and 23.05°. A similar decrease in crystallinity of starch nanoparticles obtained after ball milling was observed by Jhan et al, 8,31 with the crystallinity values from 30.23−16.08% and 33.48−18.56% over a typical angle range of 10−45°(angle of diffraction). Ball milling has shown to decrease the crystallinity of materials.…”
Section: ■ Results and Discussionsupporting
confidence: 86%
“…This may be attributed to a structural difference of the β-glucan from various sources and extent of interaction between rutin and β-glucan. Farrag et al [7] reported the difference in encapsulation efficiency of folic acid loaded on starch nanoparticles. These results displayed the capability of β-glucan to hold the rutin in its core due to the honeycomb structure [24] .…”
Section: Resultsmentioning
confidence: 99%
“…Also, rutin is unpleasant due to its astringent taste and undesirable sensorial attributes which further limits its use in food systems [3] , [4] . To overcome such obstacles, rutin has been entrapped within different carriers like starch, egg albumin, olive oil, and liposomes [5] , [6] , [7] . Among different food grade delivery systems, β-glucan has gained focus as a wall material because of its honeycomb structure which can easily hold bioactive compounds resistance to heat, acid and enzymes, broad spectrum of biological activities and is a prebiotic [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…4 (1). In simulated mouth conditions for 5 min, the release was found very less which might be the free crocin adhered to protein matrix [13] . During the transit through simulated gastric conditions, in first 30 min, the nanoformulation is mediated by the pepsin which creates pores and causes the cracks in the wall material thus facilitating the crocin release by diffusion process [32] .…”
Section: Resultsmentioning
confidence: 92%
“…The encapsulation efficiency of protein nanoparticles for crocin was calculated by following the method of Jhan et al [13] . Briefly, nanoencapsulated samples (20 mg) were washed with double distilled water (10%) and subjected to centrifugation at 3000 × g for 5 min.…”
Section: Methodsmentioning
confidence: 99%